A New Approach to the Dissolution Tests Management to Obtain Kinetic and Thermodynamic Data: Release of a Model Drug from Glyceryl Behenate Matrix Tablets - Skalická, Barbora; Matzick, Kevin; Komersová, Alena; Lochař, Václav; Bartoš, Martin; Muzikova, Jitka; Haddouchi, Samir (Wiley-VCH, 2021)
This study is focused on the use of glyceryl behenate as a lipophilic excipient of matrix tablets providing controlled drug release. The aim of this study is to evaluate activation energy (EA) and changes of the thermodynamic parameters (Delta H, Delta S, Delta G) of a dissolution process. These values, which have not yet been published, can lead to better understanding of a drug release mechanism and can extend the use options of glyceryl behenate in the pharmaceutical industry. Values of Delta H, Delta S, Delta G and E-A, providing an overall thermodynamic view on the studied matrix tablets, are evaluated based on the temperature-dependences of the release rate constant of a model drug (temperature range 25 - 45 degrees C). The studied lipophilic matrix tablets contain 10% to 50% of glyceryl behenate. Dissolution testing is carried out in an aqueous solution of HCl with addition of NaCl (pH1.2). Positive values of Delta H in the range of 3.83 to 56.13 kJ mol(-1) and positive values of Delta G indicate that the dissolution of the studied glyceryl behenate matrix tablets is an endothermic process which does not proceed spontaneously (in a temperature range of 25 - 45 degrees C). The negative slope of the linear curves of enthalpy-entropy compensation confirms the entropy-driven dissolution.
Nový přístup k managmentu disolučních testů a získání kinetických a termodynamických dat:: Uvolňování modelového léčiva z matricové tablety založené na glyceryl behenátu
Keywords: Compritol 888 ATO; glyceryl behenate; lipophilic matrix tablets; thermodynamics; Compritol 888 ATO; glyceryl behenát; lipofilní matricové tablety; termodynamika